Comparative analysis of the intellectual foundations of emotion recognition among asian and russian students - N. B. Karabuschenko; T. S. Pilishvili; T. V. Chkhikvadz; S. N. Sorokoumova; Yu. A. Dyukareva (Вестник Мининского университета, 2021)
Introduction. The article presents the results of the study on empirical verification of the theoretical model developed by Karabushchenko N.B. with co-authors of the intellectual manifestation of personality in the aspect of revealing the social-intellectual features of facial expression recognition by students from Russia and Asian countries, as well as the emotional, cultural and social intelligence of personality.Materials and Methods. The empirical test of the hypothesis was carried out with Russian and Asian students of Peoples' Friendship University of Russia (242 people in total) by employing method of comparative analysis through SPSS Statistics. Results. The hypothesis about general grounds and specific features of the manifestation of structural, functional, content components, dynamic and procedural components of the proposed model of intellectual manifestation of personality in the aspect of revealing the social-intellectual features of facial expression recognition by students is confirmed. In the content component, Mongolian and South Korean students are oriented at the monocultural dialog; Chinese students are aimed at the regulated character of the dialog; Russian students are oriented at the multiculturalism of the dialog. In the structural component,the activity in communication of Mongolian students is aimed at themselves in dialog; the activity of Russian and Chinese students is oriented atrelationship with the partner, with unrestrained feelings and pleasures from dialog for Russian students; Vietnamese students’ activity is aimed atthe limited emotional activity.From the point of view of the function of communication and anticipation, Mongolian students are oriented toward the introverted nature of interaction;Russian students areoriented toward the extraverted nature of interaction; South Korean students are oriented toward high emotional alignment with a communication partner; Vietnamese students are oriented toward the unmanifested emotional nature of interaction. In the dynamic and procedural components of the model, Mongolian students are oriented to the current situation of communication; Russian, Chinese and Vietnamese students - to anticipation of the further promotion of dialog; South Korean students - to the reflecting-anticipating situation of communication. Discussion and Conclusions. The results of the study are used in the practice of psychological consultation with Russian and Asian students based on the psychological support room.